The Coordination Role of Stress Tests in Bank Risk‐Taking - CORONA, CARLOS; NAN, LIN; ZHANG, GAOQING (Journal of Accounting Research, 2019)
ABSTRACT We examine whether stress tests distort banks' risk‐taking decisions. We study a model in which a regulator may choose to rescue banks in the event of concurrent bank failures. Our analysis reveals a novel coordination role of stress tests. Disclosure of stress‐test results informs banks of the failure likelihood of other banks, which can reduce welfare by facilitating banks' coordination in risk‐taking. However, conducting stress tests also enables the regulator to more effectively intervene banks, coordinating them preemptively into taking lower risks. We find that, if the regulator has a strong incentive to bail out, stress tests improve welfare, whereas if the regulator's incentive to bail out is weak, stress tests impair welfare.